The problem of refugees in contemporary international relations: brief analysis (International relations and international law Journal, 2017)
The problem of forced migrants and refugees lies far in the past. Actualization of this problem in modern international relations occurred in the period between two world wars, when development and formation of general approaches and institutions took place, and also after the World War II within the UN framework. This issue acquires special significance and multidimensionality in the context of development of globalization processes on the background of increase of conflict zones in all regions of the world, climatic and social changes. The volumes of forced migration and refugees flows acquire enormous scales and consequences. There is an urgent need to rethink theoretical approaches, including conceptual apparatus, legal aspects and practical approaches with the participation of the entire international community.
Keywords: Migration Issues; Refugees; Forced Migration; UNHCR